1996
DOI: 10.1051/jp1:1996102
|View full text |Cite
|
Sign up to set email alerts
|

Modelling ? Phase Organic Conductors

Abstract: The polarized optical conductivity data of two ~-phase charge-transfer salts of b~s-(ethylenedithio)-tetrathiafulvalene: ~-(BEDT-TTF)2(Hg(SCN)2Br] and ~-(BEDT-TTF)2 [Hg(SCN)C12), are, discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…It was already shown for molecular chains that the high-frequency band vanishes when the dimerization is reduced; 60 calculations were also performed on a two-dimensional κ-like structure leading to similar conclusions. 61 The same result is obtained by the cluster model, 58 when extending it to tetramers and hexamers; the electronic transitions summing up the intradimer and interdimer excitations shift to lower frequencies and get broader compared to the pure intradimer one.…”
Section: B Mid-infrared Band: Our Experimental Resultssupporting
confidence: 66%
“…It was already shown for molecular chains that the high-frequency band vanishes when the dimerization is reduced; 60 calculations were also performed on a two-dimensional κ-like structure leading to similar conclusions. 61 The same result is obtained by the cluster model, 58 when extending it to tetramers and hexamers; the electronic transitions summing up the intradimer and interdimer excitations shift to lower frequencies and get broader compared to the pure intradimer one.…”
Section: B Mid-infrared Band: Our Experimental Resultssupporting
confidence: 66%
“…At even lower temperatures a zero-frequency contribution is observed for κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Br x Cl 1−x with x = 0.73, 0.85, and 0.9, but not for the lower concentrations of Br where an energy gap opens at the metal-insulator transition. Using the cluster model suggested by Rice, Yartsev and coworkers, 28,29,30 we showed that the electronic band with a maximum at around 3500 cm −1 (E c) and the narrow features at frequencies of BEDT-TTF molecular vibrations are due to the charge transfer within a dimer coupled to A g vibrations of BEDT-TTF. This analysis permits to disentangle the intradimer and interdimer carriers contributions to the spectra, as demonstrated Refs.…”
Section: Introductionmentioning
confidence: 81%
“…In order to describe the optical properties of the j-phase organic conductors, we have proposed recently [21] the model of orthogonal dimers. In the present paper, we simplify further the model of orthogonal dimers considering the limiting case of infinite on-site correlation energy, Hubbard U, which allows to obtain a solution in analytical form.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we simplify further the model of orthogonal dimers considering the limiting case of infinite on-site correlation energy, Hubbard U, which allows to obtain a solution in analytical form. A limitation of the cluster size to two or three dimers, imposed by a rapid increase of the computation time for larger clusters, is not too bad (if we are interested in physical mechanisms of changes in the optical response upon compound modifications) for at least two reasons: (i) we take into account explicitly electronic correlations which really exist in these compounds and the infinite U limit is better than the one-electron theory because the U 0 spectrum is a worse approximation for a practically reasonable U 4t case than U 3 I [21]; and (ii) we include an interaction between dimers. So, we take into account (clearly in a rather crude fashion) both equally important interactions in these compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation